ANALISIS KESELARASAN PENGGUNAAN LAHAN DENGAN RENCANA TATA RUANG WILAYAH (RTRW) KOTA SOLOK TAHUN 2012-2031 - Devi Irmayani Saiser; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The purpose of this research is 1) determine the Solok City land use classification in 2012 and 2017, 2) determine the level of land use alignment in Solok City in 2012-2017 against the Solok City RTRW in 2012-2031, 3) find out the factors that cause the low level of land use alignment Solok City in 2012-2017 against Solok City RTRW in 2012-2031. The approach used in this study is a mix method that is a combination of qualitative and quantitative approaches using overlay methods. The results of this study note that in Solok City there are 13 (thirteen) types of land use in 2012-2017, the level of land use harmony in Solok City in 2012-2017 against RTRW of Solok City in 2012-2031 is included in the very low category, while the factors that are resulting in a low level of land use alignment to the RTRW is limited land that can be cultivated while the need for land continues to increase, population growth, people who sell land and people who have used the land before the RTRW is enacted.